Usability Evaluation of the Institutional Repository of Brasília’s University - Chaves Café, Luísa; Kafure Muñoz, Ivette (Revista General de Información y Documentación, 2017)
Presents research on information retrieval in the Institutional Repository of the University of Brasilia. The research question is: how does the interaction between postgraduates users and the repository of the University of Brasilia occurs? The research’s overall objective is to describe the interaction between users and the Repository during the process of information retrieval. To achieve the overall objective, it was necessary to identify the profile of RIUnB’s users, to characterize the repository interface, to identify the mental model of RIUnB’s users, and to identify possible difficulties of use of the interface during the information retrieval process. It was developed through a case study using online survey, participant observation and heuristic evaluation. The results show that the participants are master and doctoral students from different fields of knowledge and mainly from 25 to 35 years old. The students frequently research scientific literature in the Internet, but they rarely access repositories. They access RIUnB through Google to research an specific document, a subject or an author. The heuristic evaluation indicates has the interface has different usability problems, the most severe are related to the search system. During the observations it was found that users change their perceptions about the repository during the execution of research tasks, but have difficulties during the research process. Concludes that the interaction between graduate students and the RIUnB allows users to retrieve documents, but with difficulties. Therefore, the RIUnB is an information service that may attend the informational needs from its users. However, it is necessary to insert functions and improve usability to facilitate the interaction with the repositorie’s interface.